Coating material, preparation method and application
By preparing a double-layer clad structure on a nickel-cobalt-manganese ternary positive electrode material, and using the sintering method to coat the positive electrode active material, the problems of poor thermal stability and capacity attenuation of the material are solved, and the rate performance and structural stability of the material are improved.
Patent Information
- Application Number
- CN202411705587.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-25
AI Technical Summary
During the charging and discharging process, the nickel-cobalt-manganese ternary cathode material has caused the dissolution of transition metals, the lithium-nickel mixed discharge, and the side reaction between the material surface and the electrolyte, resulting in poor thermal stability and rapid capacity attenuation.
By sintering a mixture containing an aluminum source, a titanium source and a metal salt, a clad material is prepared and coated on the positive electrode active material to form a double-layer clad structure, including a first clad layer and a second clad layer.
This method effectively promotes the migration of lithium ions, improves the rate performance of the material, and reduces the direct contact between the electrolyte and the active material, reduces the occurrence of side reactions, and improves the interface stability and structural stability of the material.
Smart Images

Figure CN119503873A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of positive electrode materials, and in particular to coating materials, preparation methods and applications. Background Art
[0002] Nickel-cobalt-manganese ternary cathode materials have attracted extensive attention from researchers due to their high energy density and low production cost. However, during the charge and discharge process, the material will cause the dissolution of transition metals, the mixing of lithium and nickel, and the side reaction between the material surface and the electrolyte, resulting in poor thermal stability and rapid capacity decay due to the release of lithium ions and the loss of lattice oxygen.
[0003] A common method to improve the structural stability of nickel-cobalt-manganese ternary positive electrode materials is to coat their surface with a layer of coating material. However, there are often problems such as uneven coating effect, poor conductivity of the coating material, and complex process, which lead to decreased thermal stability of the material and poor rate performance.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a coating material, a preparation method and an application thereof. The coating material is applied to a positive electrode material, which is beneficial to improving the stability of the positive electrode material.
[0006] The present invention is achieved in that:
[0007] In a first aspect, the present invention provides a method for preparing a coating material, comprising: sintering a mixture containing an aluminum source, a titanium source and a metal salt to obtain the coating material.
[0008] In an optional embodiment, the sintering temperature is 700° C.-1200° C., and the sintering time is 3 h-36 h.
[0009] In an optional embodiment, in the mixture, Al 3+ and Ti 4+ The molar ratio is (0.1-1):1, and the mass fraction of the metal salt is ≤5wt%.
[0010] In an optional embodiment, the aluminum source is selected from at least one of Al2O3, Al2(SO4)3, Al(OH)3 and Al2(CO3)3;
[0011] and / or, the titanium source is selected from at least one of TiO2, Ti2(SO4)3, TiO, Ti2O3 and Ti(NO3)4;
[0012] And / or, the metal salt is selected from at least one of Mg(NO3)2, La(CH3COO)3 and Zn(NO3)2.
[0013] In a second aspect, the present invention provides a coating material prepared by the method described in any one of the aforementioned embodiments.
[0014] In a third aspect, the present invention provides a positive electrode material, comprising: a positive electrode active material, a first coating layer coated on the surface of the positive electrode active material, and a second coating layer coated on the outside of the first coating layer, wherein the first coating layer comprises the coating material described in any one of the aforementioned embodiments, and the second coating layer is a carbon coating layer.
[0015] In an optional embodiment, the positive electrode active material is a nickel-cobalt-manganese ternary positive electrode material.
[0016] In a fourth aspect, the present invention provides a method for preparing the positive electrode material according to the aforementioned embodiment, comprising:
[0017] Coating with a coating material, mixing the positive electrode active material with the coating material and performing a first calcination to obtain a positive electrode material coated with a first coating layer;
[0018] Carbon coating: the positive electrode material coated with the first coating layer is mixed with a carbon source and subjected to a second calcination to obtain the positive electrode material having a double coating layer.
[0019] In an optional embodiment, the mass ratio of the positive electrode active material to the coating material is (50-2000):1;
[0020] and / or, the first calcination temperature is 400° C.-800° C., and the first calcination time is 2 h-12 h;
[0021] And / or, in the coating material coating step, the positive electrode active material and the coating material are mixed, added into anhydrous ethanol, stirred, and then dried, and then the dried material is first calcined; wherein the mass ratio of the added amount of anhydrous ethanol to the positive electrode active material is (0.5-5):1;
[0022] And / or, the mass ratio of the positive electrode material coated by the first coating layer to the carbon source is (20-2000):1;
[0023] and / or, the second calcination temperature is 200° C.-500° C., and the second calcination time is 2 h-12 h;
[0024] And / or, in the carbon coating step, the positive electrode material coated with the first coating layer is mixed with the carbon source, added into anhydrous ethanol, stirred and dried, and then the dried material is subjected to a second calcination; wherein the mass ratio of the added amount of anhydrous ethanol to the positive electrode material coated with the first coating layer is (0.5-5):1.
[0025] In a fifth aspect, the present invention provides a secondary battery comprising the positive electrode material described in the aforementioned embodiment.
[0026] The present invention has the following beneficial effects:
[0027] The coating material obtained by the method of the present application can firstly effectively promote the migration of lithium ions and improve the rate performance of the material; secondly, the coating material itself has good physical and chemical stability, and when used in the positive electrode material, it can effectively reduce the direct contact between the electrolyte and the active material, which is beneficial to reduce the occurrence of side reactions and improve the interface stability and structural stability of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 This is the XRD pattern of the coating material prepared in Example 1 of the present application;
[0030] Figure 2 This is a SEM image of the coating material prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0032] An embodiment of the present invention provides a method for preparing a coating material, comprising: sintering a mixture containing an aluminum source, a titanium source and a metal salt to obtain the coating material.
[0033] The coating material obtained by the method of the present application can firstly effectively promote the migration of lithium ions and improve the rate performance of the material; secondly, the coating material itself has good physical and chemical stability, and when used in the positive electrode material, it can effectively reduce the direct contact between the electrolyte and the active material, which is beneficial to reduce the occurrence of side reactions and improve the interface stability and structural stability of the material.
[0034] In an optional embodiment, the sintering temperature is 700° C.-1200° C., and the sintering time is 3 h-36 h.
[0035] In an optional embodiment, in the mixture, Al 3+ and Ti 4+ The molar ratio is (0.1-1):1, and the mass fraction of the metal salt is ≤5wt%.
[0036] Among them, if the proportion of aluminum source is too large and the proportion of titanium source is too small, the ionic conductivity of the coated positive electrode material will be low, which will hinder the transmission of lithium ions, increase the internal resistance of the battery, and affect the rate performance of the positive electrode material; if the amount of metal salt is too much, it will lead to a decrease in the capacity of the material and increase the production cost of the material. If the amount of metal salt is too small, it will affect the electrical conductivity of the material. Therefore, the proportion of aluminum source, titanium source and metal salt in the coating material needs to be moderate.
[0037] In an optional embodiment, the aluminum source is selected from at least one of Al2O3, Al2(SO4)3, Al(OH)3 and Al2(CO3)3;
[0038] and / or, the titanium source is selected from at least one of TiO2, Ti2(SO4)3, TiO, Ti2O3 and Ti(NO3)4;
[0039] And / or, the metal salt is selected from at least one of Mg(NO3)2, La(CH3COO)3 and Zn(NO3)2.
[0040] An embodiment of the present invention further provides a coating material, which is prepared by the method described in any one of the aforementioned embodiments.
[0041] The specific structure and composition of the coating material have not yet been determined. According to existing test results, the coating material includes (AlTi)O and titanium oxide, as well as some other unknown components.
[0042] An embodiment of the present invention also provides a positive electrode material, comprising: a positive electrode active material, a first coating layer coated on the surface of the positive electrode active material, and a second coating layer coated on the outside of the first coating layer, wherein the first coating layer includes the coating material described in any one of the aforementioned embodiments, and the second coating layer is a carbon coating layer.
[0043] The positive electrode material in the present application includes a coating material layer and a carbon coating layer. The synergistic effect of the double coating layers is beneficial to further improve the structural stability and thermal stability of the ternary positive electrode material, and is more beneficial to improving the cycle stability of the positive electrode material.
[0044] In an optional embodiment, the positive electrode active material is a nickel-cobalt-manganese ternary positive electrode material.
[0045] In the present application, the coating material layer and the carbon coating layer coated on the positive electrode active material are beneficial to improving the cycle performance of the positive electrode material. When applied to the nickel-cobalt-manganese ternary positive electrode material, the effect of improving its cycle performance is more significant.
[0046] Among them, the nickel-cobalt-manganese ternary positive electrode material can be a commercially available material, and can also be prepared according to the following method: lithium salt (Li2CO3, LiOH, LiNO3, etc.) and ternary precursor are mechanically mixed in a certain proportion and then sintered at high temperature (700-1200°C, 3-36h).
[0047] An embodiment of the present invention further provides a method for preparing the positive electrode material described in the aforementioned embodiment, comprising:
[0048] Coating with a coating material, mixing the positive electrode active material with the coating material and performing a first calcination to obtain a positive electrode material coated with a first coating layer;
[0049] Carbon coating: the positive electrode material coated with the first coating layer is mixed with a carbon source and subjected to a second calcination to obtain the positive electrode material having a double coating layer.
[0050] The preparation method of the positive electrode material in the present application has a simple process, and only two steps of calcination are required to complete the preparation of the positive electrode material.
[0051] In an optional embodiment, the mass ratio of the positive electrode active material to the coating material is (50-2000): 1; if the amount of coating material is too little, the effect of improving the rate performance and cycle performance of the positive electrode material is not significant; but if the amount of coating material is too much, on the one hand, the coating material cannot provide a higher capacity, which will lead to a decrease in material capacity, and on the other hand, further increasing the amount of coating material will reduce the marginal effect of improving the rate performance and cycle performance. Therefore, the amount of coating material should not be too much.
[0052] And / or, the first calcination temperature is 400°C-800°C, and the first calcination time is 2h-12h; the increase in the first calcination temperature is beneficial to improving the bonding strength between the coating material and the positive electrode active material, which is beneficial to improving the cycle performance of the positive electrode material, but if the calcination temperature is too high, it may also destroy the structure of the positive electrode active material.
[0053] And / or, in the coating material coating step, the positive electrode active material and the coating material are mixed, added into anhydrous ethanol, stirred and then dried, and then the dried material is subjected to a first calcination; wherein the mass ratio of the added anhydrous ethanol to the positive electrode active material is (0.5-5):1; the main purpose of this step is to fully mix the positive electrode active material and the coating material.
[0054] And / or, the mass ratio of the positive electrode material coated by the first coating layer to the carbon source is (20-2000): 1; if the amount of carbon source is too small, the effect of improving the cycle performance of the positive electrode material is not significant; but if the amount of carbon source is too large, it will also lead to a decrease in the material capacity, so the amount of carbon source should not be too much. In the embodiment of the present application, the carbon source can be selected from glucose, sucrose, citric acid and graphene.
[0055] And / or, the second calcination temperature is 200℃-500℃, and the second calcination time is 2h-12h; the increase in the second calcination temperature is beneficial to improving the bonding strength between the carbon source and the coating material layer, which is beneficial to improving the cycle performance of the positive electrode material. If the calcination temperature is too high, it is not conducive to cost reduction.
[0056] And / or, in the carbon coating step, the positive electrode material coated with the first coating layer is mixed with the carbon source, added into anhydrous ethanol, stirred and dried, and then the dried material is subjected to a second calcination; wherein the mass ratio of the added anhydrous ethanol to the positive electrode material coated with the first coating layer is (0.5-5): 1. The main purpose of this step is to fully mix the positive electrode active material with the coating material.
[0057] An embodiment of the present invention further provides a secondary battery, comprising the positive electrode material described in the above embodiment.
[0058] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0059] Example 1
[0060] This embodiment provides a method for preparing a positive electrode material, which specifically includes the following steps:
[0061] Step 1, preparation of positive electrode active material: 50.0g of ternary precursor (Ni 0.8 Co 0.1 Mn 0.1 (OH)2) was mixed with 20.1gLi2CO3, sintered at 800°C for 18h, and then naturally cooled and crushed to obtain the positive electrode active material;
[0062] Step 2, preparation of coating material: 20.0g Al2O3, 94.0g TiO2 and 3.4g Mg(NO3)2 were mixed uniformly, sintered at 1000℃ for 10h, cooled naturally and crushed to obtain coating material, the XRD pattern of which is shown in Figure 1 As shown in the SEM images Figure 2 As shown;
[0063] Step 3, coating with coating material: the positive electrode active material, the coating material and anhydrous ethanol are mixed in a mass ratio of 100:1:101, and then dried at 55°C for 12 hours, and then the dried material is calcined at 500°C for 6 hours to obtain a positive electrode material coated with a first coating layer;
[0064] Step 4, carbon coating: the positive electrode material coated with the first coating layer, glucose and anhydrous ethanol are mixed in a mass ratio of 200:1:201, and then dried at 60°C for 10 hours, and then the dried material is calcined at 400°C for 8 hours in an argon atmosphere to obtain the positive electrode material with a double coating layer.
[0065] Example 2
[0066] This embodiment provides a method for preparing a positive electrode material, which specifically includes the following steps:
[0067] Step 1, preparation of positive electrode active material: 50.0g of ternary precursor (Ni 0.8 Co 0.1 Mn 0.1 (OH)2) was mixed with 20.1gLi2CO3, and then sintered at 850°C for 15h, and then naturally cooled and crushed to obtain the positive electrode active material;
[0068] Step 2, preparing the coating material: 20.0 g Al2(SO4)3, 127.2 g Ti2(SO4)3 and 7.0 g Zn(NO3)2 were mixed uniformly, sintered at 1200°C for 18 h, and naturally cooled and crushed to obtain the coating material;
[0069] Step 3, coating with coating material: the positive electrode active material, the coating material and anhydrous ethanol are mixed in a mass ratio of 200:1:150, and then dried at 50°C for 18 hours, and then the dried material is calcined at 600°C for 5 hours to obtain a positive electrode material coated with a first coating layer;
[0070] Step 4, carbon coating: the positive electrode material coated with the first coating layer, sucrose and anhydrous ethanol are mixed in a mass ratio of 500:1:400, and then dried at 65°C for 8 hours, and then the dried material is calcined at 450°C for 6 hours in a nitrogen atmosphere to obtain the positive electrode material with a double coating layer.
[0071] Example 3
[0072] This embodiment provides a method for preparing a positive electrode material, which specifically includes the following steps:
[0073] Step 1, preparation of positive electrode active material: 50.0g of ternary precursor (Ni 0.8 Co 0.1 Mn0.1 (OH)2) was mixed with 20.1gLi2CO3, sintered at 900℃ for 12h, cooled naturally and crushed to obtain the positive electrode active material;
[0074] Step 2, preparing the coating material: 20.0 g Al(OH)3, 18.4 g Ti2O3 and 0.38 g La(CH3COO)3 were mixed uniformly, sintered at 900°C for 24 h, and naturally cooled and crushed to obtain the coating material;
[0075] Step 3, coating with coating material: the positive electrode active material, the coating material and anhydrous ethanol are mixed in a mass ratio of 500:1:1000, and then dried at 55°C for 18 hours, and then the dried material is calcined at 700°C for 10 hours to obtain a positive electrode material coated with a first coating layer;
[0076] Step 4, carbon coating: the positive electrode material coated with the first coating layer, graphene and anhydrous ethanol are mixed in a mass ratio of 1000:1:800, and then dried at 60°C for 8 hours, and then the dried material is calcined at 500°C for 10 hours in an argon atmosphere to obtain the positive electrode material with a double coating layer.
[0077] Comparative Example 1
[0078] This comparative example provides a method for preparing a positive electrode material, which differs from Example 1 mainly in that steps 2-4 are omitted.
[0079] Comparative Example 2
[0080] This comparative example provides a method for preparing a positive electrode material, which differs from Example 1 mainly in that steps 2-3 are omitted, and the positive electrode material coated with the first coating layer in step 4 is replaced by the positive electrode active material in step 1.
[0081] Comparative Example 3
[0082] This comparative example provides a method for preparing a positive electrode material, which is different from Example 1 mainly in that step 4 is omitted.
[0083] Comparative Example 4
[0084] This comparative example provides a method for preparing a positive electrode material, which is different from Example 1 mainly in that no metal salt is added in step 2.
[0085] Comparative Example 5
[0086] This comparative example provides a method for preparing a positive electrode material, which is different from Example 1 mainly in that no aluminum source is added in step 2.
[0087] Comparative Example 6
[0088] This comparative example provides a method for preparing a positive electrode material, which is different from Example 1 mainly in that no titanium source is added in step 2.
[0089] Comparative Example 7
[0090] This comparative example provides a method for preparing a positive electrode material, which differs from Example 1 mainly in that step 2 is omitted and the coating material in step 3 is (Al2Ti)O5.
[0091] Comparative Example 8
[0092] This comparative example provides a method for preparing a positive electrode material, which is different from Example 1 mainly in that in step 2, the amount of Al2O3 used is 50.0 g, the amount of TiO2 used is 19.6 g, and the amount of Mg(NO3)2 used is 7.0 g.
[0093] The positive electrode materials prepared in the above embodiments and comparative examples were made into batteries, and the performance of the batteries was tested. The test results are shown in Table 1.
[0094] Battery assembly methods include:
[0095] Using the ternary positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 8 as the positive electrode, the metal lithium sheet as the negative electrode, and 1.0 mol / L LiPF6 / EC (ethylene carbonate) + DMC (dimethyl carbonate) + FEC (fluoroethylene carbonate) (EC, DMC and FEC volume ratio 4.5:4.5:1) as the electrolyte, they were assembled into CR2032 button batteries in an argon glove box.
[0096] Test methods include:
[0097] Rate test: The button battery was subjected to constant current charge and discharge tests at current densities of 0.1, 0.2, 0.5, 1 and 2C, with a voltage range of 3 to 4.3V.
[0098] Cycle test: The button battery is subjected to a constant current charge and discharge cycle at a current density of 0.1C for 1 cycle, and then to a constant current charge and discharge cycle at a current density of 1C for 100 cycles, with a voltage range of 3 to 4.3V.
[0099] Table 1
[0100]
[0101] It is not difficult to see from Table 1 that the battery prepared using the ternary positive electrode material with double coating layers obtained in Examples 1-3 has better rate performance and cycle performance than the battery prepared using the material obtained in Comparative Examples 1-8.
[0102] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a coating material, characterized in that: include: The coating material is obtained by sintering a mixture containing an aluminum source, a titanium source and a metal salt.
2. The method for preparing the coating material according to claim 1, characterized in that: The sintering temperature is 700°C-1200°C, and the sintering time is 3h-36h.
3. The method for preparing the coating material according to claim 1, characterized in that: In the mixture, Al 3+ and Ti 4+ The molar ratio is (0.1-1):1, and the mass fraction of the metal salt is ≤5wt%.
4. The method for preparing the coating material according to claim 1, characterized in that: The aluminum source is selected from at least one of Al2O3, Al2(SO4)3, Al(OH)3 and Al2(CO3)3; and / or, the titanium source is selected from at least one of TiO2, Ti2(SO4)3, TiO, Ti2O3 and Ti(NO3)4; And / or, the metal salt is selected from at least one of Mg(NO3)2, La(CH3COO)3 and Zn(NO3)2.
5. A coating material, characterized in that: Prepared by the method according to any one of claims 1 to 4.
6. A positive electrode material, characterized in that include: A positive electrode active material, a first coating layer coated on the surface of the positive electrode active material, and a second coating layer coated outside the first coating layer, wherein the first coating layer includes the coating material according to claim 5, and the second coating layer is a carbon coating layer.
7. The positive electrode material according to claim 6, characterized in that The positive electrode active material is a nickel-cobalt-manganese ternary positive electrode material.
8. A method for preparing the positive electrode material according to claim 6 or 7, characterized in that: include: Coating with a coating material, mixing the positive electrode active material with the coating material and performing a first calcination to obtain a positive electrode material coated with a first coating layer; Carbon coating: the positive electrode material coated with the first coating layer is mixed with a carbon source and subjected to a second calcination to obtain the positive electrode material having a double coating layer.
9. The method for preparing the positive electrode material according to claim 8, characterized in that: The mass ratio of the positive electrode active material to the coating material is (50-2000):1; and / or, the first calcination temperature is 400° C.-800° C., and the first calcination time is 2 h-12 h; And / or, in the coating material coating step, the positive electrode active material and the coating material are mixed, added into anhydrous ethanol, stirred, and then dried, and then the dried material is first calcined; wherein the mass ratio of the added amount of anhydrous ethanol to the positive electrode active material is (0.5-5):1; And / or, the mass ratio of the positive electrode material coated by the first coating layer to the carbon source is (20-2000):1; and / or, the second calcination temperature is 200° C.-500° C., and the second calcination time is 2 h-12 h; And / or, in the carbon coating step, the positive electrode material coated with the first coating layer is mixed with the carbon source, added into anhydrous ethanol, stirred and dried, and then the dried material is subjected to a second calcination; wherein the mass ratio of the added amount of anhydrous ethanol to the positive electrode material coated with the first coating layer is (0.5-5):
1.
10. A secondary battery, characterized in that: Comprising the positive electrode material according to claim 6 or 7.